(untitled) (Annals of Medical Research, 2024)
Aim: It was aimed to investigate the difference between erectile function, orgasmic function, sexual desire, sexual satisfaction and general satisfaction, and depression, anxiety and stress before and after bariatric surgery in men with and without diabetes mellitus (DM). Material and Methods: A total of 80 male patients, 40 individuals who underwent bariatric surgery and were diagnosed with type 2 diabetes and 40 individuals who did not, were included in the study. Patients were evaluated with the International Erectile Function Form and Depression Anxiety Stress Scale before and 6 months after the operation. The difference between stress, anxiety, depression and sexual function values of diabetic and non-diabetic groups undergoing bariatric surgery was analyzed before and after the operation. Results: In the non-diabetic group, there was a difference between pre- and post-bariatric surgery in depression and erectile function, orgasmic function, sexual desire, sexual satisfaction and general satisfaction scores (p = 0.000), apart from stress (p = 0.720) and anxiety (p = 0.675). In the diabetic group, a difference was found in all subscale scores except sexual desire (p = 0.160). When the groups are compared after surgery; while stress and anxiety scores decreased more in the diabetic group; erectile function, orgasmic function, sexual desire, sexual satisfaction and general satisfaction scores increased more in the nondiabetic group. Conclusion: The presence of DM in men undergoing bariatric surgery may limit the improvement in sexual functions after surgery; however, diabetic individuals may benefit more from surgery in terms of depression, stress and anxiety.